Smoke and heat detector/ Mohd Nor Azam Md Tahir and Mohd Zaim Abd Wahab - Md Tahir, Mohd Nor Azam; Abd Wahab, Mohd Zaim (2003)
Nowadays, there is numerous unpredictable disaster occur suddenly, just in a split seconds. One of them is the tire blasting. The ‘Smoke and Heat Detector’ is a security system designed to detect the presence of any fire using the smoke and heat detector. Both detectors will ‘play’ their own functioning system. This circuit will active if either of these detectors activated. In this thesis, a new detection technique is designed using multi-sensor techniques. By combining this two detector will make this ‘life watcher’ be more efficient and aware. When smoke detector being activated, it will produce a warn siren through its buzzer. For the heat detector, when it detector the changes in room temperature; normal t hot; it will activate the circuit and start to produce a siren warn. As the heat circuit activated, it will cause the relay to rotate from a normal leg and connect the circuit to motor which we use the fan. As a remit, the fan will rotating and starts to ‘push’ away the smoke and at the same time, cooling the temperature in the room.